Differences in Organizing Between Unions and NGOs: Conflict and Cooperation Among Swedish Unions and NGOs - Egels-Zandén, Niklas; Hyllman, Peter (2011)
The protection of workers’ rights is at the heart of the ongoing debate on business ethics. In balancing transnational corporations’ (TNCs) influence in private regulatory systems intended to protect workers’ rights in emerging economies, several authors have emphasized the importance of cooperative relationships between unions and NGOs. In practice, however, conflict has often entered into union–NGO relations, weakening the protection of workers’ rights. We argue that cooperative union–NGO relationships are difficult to form in part because of the differences existing between how unions and NGOs organize. More specifically, based on two qualitative studies, we demonstrate that the problems stem from differences in organizing related to (i) identity construction, (ii) governance systems, and (iii) resources. The article concludes with a discussion on the possibility of successful union–NGO cooperation and improved protection of workers’ rights in emerging economies.
Keywords: Union; transnational corporations; supplier relations; NGO; labour practice; international framework agreement; Corporate Responsibility; Code of conduct